Management of Diabetic Foot Ulcers Using Topical Oxygen Therapy: A Case Series - Tabanjeh, Sinan F.; Al-Malki, Talal; Alhazzani, Abdulmajeed R.; Robert, Asirvatham A. (Current Diabetes Reviews, 2022)
Background and Aim: Surgical and endovascular revascularization procedures along with hyperbaric oxygen therapy (HBOT) and topical oxygen therapy (TOT) for chronic oxygen-deprived wounds are standard care treatment protocols for diabetic foot ulcer (DFU). Topical developments in the delivery of topical oxygen therapy have made this a more feasible treatment in practice. The present case series highlights the efficacy of NATROX therapy as TOT in wound healing and the impact of increased oxygenation on ulcer healing in patients with diabetic foot ulcers. Methods: The TOT was evaluated in 6 patients with DFU who have applied NATROX topical oxygen delivery system for a period ranging from 6 weeks to 24 weeks at Kahel Specialized Centre, located in Olaya, Riyadh, Saudi Arabia. Results: The administration of TOT demonstrated complete wound healing in all the six patients who either had ulcers with minor amputation of toes/heel or had ulcers with other comorbidities in a range from 3 to 8 weeks. Conclusion: NATROX therapy is an advanced topical oxygen delivery system compared to other conventional oxygen delivery systems; however, the study warrants further research to assess its potential applicability in DFU wound healing in large sample size and across the races.
Keywords: oxygenation topical oxygen therapy